Impacts of COVID-19 on Work and Wages in Cox's Bazar - World Bank (World Bank, Washington, DC, 2021)
A rapid phone survey was implemented on a representative sample of recently displaced Rohingya households and their host communities in the Cox’s Bazar district of Bangladesh, to track the impacts of the COVID-19 crisis on labor markets, wages, and household coping strategies. This survey built on the Cox’s Bazar Panel Survey (CBPS), which is a multi-topic survey that focused on socio-economic outcomes and access to health services. This first round of the rapid phone survey, was conducted from 21 April-20 May 2020 (a month into the 2-month long COVID-19 lockdown). A sub-sample of 3,005 out of the 5,020 households surveyed at baseline were covered by this survey. In this first tracking survey 3,009 out of the 9,045 adults surveyed in baseline were covered.